2020
DOI: 10.1111/jfbc.13508
|View full text |Cite
|
Sign up to set email alerts
|

Ethanolic extract of Betel ( Piper betle L.) and Chaphlu ( Piper sarmentosum Roxb.) dechlorophyllized using sedimentation process: Production, characteristics, and antioxidant activities

Abstract: Sedimentation process was used to remove chlorophyll from betel leaf ethanolic extracts (BLEE) and chaphlu leaf ethanolic extracts (CLEE). The influence of water quantity on chlorophyll content, total phenolic content (TPC), and antioxidant activity of the extracts was studied. The sedimentation process showed a remarkable reduction in chlorophyll A, chlorophyll B, and total chlorophyll contents of both extracts. Nevertheless, no differences in chlorophyll content, TPC, and antioxidant activities were observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 51 publications
3
37
0
Order By: Relevance
“…Consequently, the appropriate extract time was chosen as 2 h for P. betle and 1 h for P. sarmentosum. The correlation between polyphenol contents and DPPH scavenging activities of Pb.ext and Ps.ext suggested that the phenolic compounds of both extracts were responsible for their antioxidant activities [23]. These results also revealed that P. betle has stronger antioxidant activity as well as reducing power than P. sarmentosum.…”
Section: Appropriate Extraction Timementioning
confidence: 69%
See 1 more Smart Citation
“…Consequently, the appropriate extract time was chosen as 2 h for P. betle and 1 h for P. sarmentosum. The correlation between polyphenol contents and DPPH scavenging activities of Pb.ext and Ps.ext suggested that the phenolic compounds of both extracts were responsible for their antioxidant activities [23]. These results also revealed that P. betle has stronger antioxidant activity as well as reducing power than P. sarmentosum.…”
Section: Appropriate Extraction Timementioning
confidence: 69%
“…Even though P. betle has been well studied and applied in several commercial products with antibacterial and antifungal effects, P. sarmentosum has been still little-known in this field. Moreover, there have been several researches compared the vegetative anatomy, phenolic contents, and bioactivities between P. betle and P. sarmentosum [22,23], but their capacities in AgNP synthesis have been not compared yet.…”
Section: Introductionmentioning
confidence: 99%
“…Top fraction of ethanolic extract of Betel ( Piper betle L.) and Chaphlu ( Piper sarmentosum Roxb.) leaves obtained after sedimentation process also had lower Chlo‐a, Chlo‐b and Tot‐Chlo contents than the crude extract without chlorophyll removal (Tagrida & Benjakul, 2020). For all the extracts, Chlo‐b content was higher than that of Chlo‐a.…”
Section: Resultsmentioning
confidence: 99%
“…The high antioxidant activities for kaempferol and quercetin identified in noni leaf extract were reported (Deng et al, 2008). Tatsimo et al (2012) documented the excellent antioxidant and antimicrobial activities for kaempferol rhamnoside derivatives isolated from Bryophyllum pinnatum. Quercetin was documented to possess high antimicrobial activities against both GPB and GNB (Wang et al, 2017).…”
Section: Identification Of Phenolic Compounds In Enle and Cr-enlementioning
confidence: 92%
“…(Madhumita et al, 2019), phenolic acid, antioxidants, and high avonoids can help in the process of material synthesis (Punuri et al, 2012). Piper betle Linn also contains high antioxidants (Tagrida and Benjakul, 2020) alkaloids, steroids, tannins, saponins, and amino acids that can inhibit the electron transport system. The chemical composition includes the phenol group with the most avonoid compounds.…”
Section: Composition and Chemical Characteris-tics Of Piper Betle Linnmentioning
confidence: 99%